2008
DOI: 10.1118/1.2885371
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of lesion size, depth, and uptake using a dual‐head molecular breast imaging system

Abstract: A method to perform quantitative lesion analysis in molecular breast imaging (MBI) was developed using the opposing views from a novel dual-head dedicated gamma camera. Monte Carlo simulations and phantom models were used to simulate MBI images with known lesion parameters. A relationship between the full widths at 25%, 35%, and 50% of the maximum of intensity profiles through lesions and the true lesion diameter as a function of compressed breast thickness was developed in order to measure lesion diameter. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 21 publications
4
38
0
Order By: Relevance
“…For 99m Tc-sestamibi-based imaging, although a method of quantification with dual-head systems has been described (56), intensity of uptake is not routinely quantified with current software. Subcutaneous fat is used as the reference standard, with backgroundparenchyma uptake and lesion uptake described qualitatively as photopenic (less than subcutaneous fat), mild, moderate, or marked.…”
Section: Standardized Interpretive Criteria and Quantificationmentioning
confidence: 99%
“…For 99m Tc-sestamibi-based imaging, although a method of quantification with dual-head systems has been described (56), intensity of uptake is not routinely quantified with current software. Subcutaneous fat is used as the reference standard, with backgroundparenchyma uptake and lesion uptake described qualitatively as photopenic (less than subcutaneous fat), mild, moderate, or marked.…”
Section: Standardized Interpretive Criteria and Quantificationmentioning
confidence: 99%
“…Previous work on the quantification of Tc99m-sestamibi uptake in MBI-detected lesions has shown that lesion depth can be estimated to within 1 mm using the ratio of counts in the conjugate views of the breast acquired from the opposed detectors. 18 However, the use of a dual-head system with the breast compressed between the two detectors substantially limits a radiologist's access to the breast for the biopsy procedure. In this work, we propose a design where one of the detectors is replaced with a compression paddle, thus reducing the MBI-guided biopsy system to a single-detector system (Fig.…”
Section: Iib Design Considerations For Mbi-guided Biopsymentioning
confidence: 99%
“…These technologies include those that detect 18 F-fluorodeoxyglucose (FDG) positron emissions such as positron emission mammography (PEM) and others that utilize single-photon emitting radiotracers (typically Tc-99m sestamibi) such as breast-specific gamma imaging (BSGI) and molecular breast imaging (MBI). [1][2][3] All of these dedicated technologies use small detectors with minimal dead space at the detector edge, permitting the breast to be placed in direct contact with the detector head, thereby allowing high spatial resolution imaging of small breast tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the development of a dual-head camera for BSGI has allowed the simultaneous acquisition of opposing breast views, providing the quantification of lesion parameters including size, depth to the collimator face and relative tracer uptake [17]. Validation of the methods by Monte Carlo and phantom simulations have shown that using the measured lesion diameter and measurements of counts in the lesion and background breast region, relative radiotracer uptake and tumour to background ratio can be accurately calculated [18].…”
mentioning
confidence: 99%
“…Therefore, the implementation of a lexicon for describing BSGI as proposed by Conners et al [10] is highly advisable for the development of this technique, because it is necessary that the terminology is easy to understand and consistently used by interpreting nuclear medicine physicians. On the other hand, a similar lexicon has recently been published for the standardized reporting of the findings of positron emission mammography (PEM), an emerging molecular imaging technology which produces high-resolution tomographic images of 18 F-FDG uptake in the breasts [13]. With increasing use of BSGI, there is clearly a need for standardized terminology to describe its outcomes, for interpretation and to provide management recommendations, similar to the standardized classification that already exists for other breast imaging modalities.…”
mentioning
confidence: 99%